Real‐Time Mimicking the Electronic Structure of N‐Coordinated Ni Single Atoms: NiS‐Enabled Electrochemical Reduction of CO2 to CO. Issue 35 (28th July 2022) - Han, Man Ho; Kim, Dongjin; Kim, Sangkuk; Yu, Seung‐Ho; Won, Da Hye; Min, Byoung Koun; Chae, Keun Hwa; Lee, Woong Hee; Oh, Hyung‐Suk
Abstract: N‐coordinated Ni single atom (Ni–NC) is one of the best catalysts for the CO2 reduction reaction (CO2 RR) to produce CO. However, no bulk Ni materials have exhibited high catalytic activity for CO2 RR. Herein, it is shown that NiS nanoparticles mimicking the electronic structure of Ni–NC in real‐time enhance the CO2 RR activity in a zero‐gap electrolyzer. In situ/Operando X‐ray absorption spectroscopy suggests that under a cathodic potential, the electronic structure of NiS changes similarly to that of Ni–NC and modulated Ox–z Sy ligands with similar properties to Ni ligands, resulting in a mimicked electronic structure. However, NiS exhibits low stability owing to the loss of S species, key to mimicking N ligands. The future challenges in finding a stable mimicked electronic structure are discussed. Moreover, this work provides new insights into the development of catalysts from materials that have not generally been considered previously. Abstract : NiS exhibits enhanced catalytic activity for CO2 reduction in a zero‐gap electrolyzer. Operando X‐ray absorption spectroscopy suggests that NiS mimics single atom catalysts with the ideal electronic structure for CO2 reduction. It is expected that the NiS successfully mimics the electronic structure of NiNC due to its broken D4h symmetry and modulated Ox–z Sy ligands under a cathodic potential.